Parental traditional medicine use for children and associated factors in Harar City, Harari Regional State, Eastern Ethiopia: a community-based cross-sectional study - Alemu, Ayichew; Meseret, Fentahun; Keneni, Mulualem; Wondimneh, Fenta; Legesse, Henok; Mossie, Yalew; Teshager, Tilahun; Tamiru, Eyerusalem; Tizau, Diribsa; Asfaw, Tesfaye (Frontiers in Pediatrics, 2025)
IntroductionGlobally, there is consensus that traditional medicine (TM) has its benefit in solving health-related issues; however, a challenge lies in the lack of standardized scientific criteria to guide its appropriate use. Evidence suggests that, in some cases, traditional medicine may exacerbate health problems and lead to complications. Although many studies have explored traditional medicine use among adults, there is limited research on parental use of traditional medicine for children, particularly in Harar City. Therefore, the aim of this study was to determine the prevalence and associated factors of parental traditional medicine use for children in Harar City, Eastern Ethiopia.Research methodsA cross-sectional study was carried out in the community of Harar City between 15 October and 15 November 2024. A multistage sampling procedure was used to obtain 348 parents. The required data were assembled through in-person interviews. The data that assembled were analyzed using Stata statistical software, version 16.0. To determine the associated factors with the outcome variable, multivariable logistic regression was applied via adjusted odds ratio (aOR) with a 95% confidence interval (CI). Independent variables with p < 0.05 were declared as significantly associated variables with the outcome variable.ResultsApproximately 348 parents were sampled for the study with a response rate of 100%. The proportion of parental TM use for children was 76.15% (95% CI: 71.8–80.5). Parents with more than four children (aOR = 3.24, 95% CI: 1.13–9.28), with a good attitude toward TM (aOR = 1.98, 95% CI: 1.02–3.86), and who were members of community-based health insurance (aOR = 0.34, 95% CI: 0.19–0.63) were independent variables associated with parental traditional medicine use for children.ConclusionApproximately three-quarters of parents reported using traditional medicine for their children. This practice was influenced by modifiable factors. Therefore, stakeholders in the health sector should give focused attention to the key factors influencing parental use of traditional medicine for children.